Psychosocial Addiction Assessment Among 17‒18-year Old Students of Novosibirsk - Alexey V. Lebedev (National Research Mordova State University, 2017)
Introduction: the article presents the results of a study of 17–18 year students from various universities of Novosibirsk and identifies the prevalence of the tendency to various forms of psychosocial dependencies among the youth. The relevance of the work is predetermined by the increased dissemination of various psychosocial addictions among the youth and formation of youth subculture of addictive behaviour. Early detection of persons exhibiting a high propensity for various forms of psychosocial addictions, will predict negative trends in the youth environment and in a timely manner provide them with psychological and pedagogical help. The aim of this work is to identify among the 1st – 2nd year students in Novosibirsk the prevalence of the propensity for dif ferent types of psychosocial dependencies. Materials and Methods: over 10 thousand students aged from 17 to 18 years participated in the sociological study in Novosibirsk. The authors developed a special computer programme to identify propensity to addictions. The obtained results were processed using methods of variationa l and difference statistics. Results: many of 17–18 year old students have no addiction. The 17–18 year old girls have a higher level of propensity to tobacco addiction compared to boys and a tendency to increase the number of people with high risk of dependence to psychoactive substances. Young men with a high propensity to dependent behaviour have a higher risk to “heavy” types of dependence than girls. Discussion and Conclusions: the described tendencies reflect the general situation in the society, associated with the formation of youth subculture of addictive behaviour. The results should be considered in preventive and educational activities in universities. Methods for identifying addictions are effective in the correctional activity of psychologists. The authors intend to investigate the behaviour of students in high schools and in universities to reveal propensity to addictions.